The effect of seed coating with different plant nutrient formulations on seed quality of tomato (Lycopersicon esculentum) seeds during storage - Klarod, Kittiwan; Siri, Boonmee; Dongsansuk, Anoma (วารสารแก่นเกษตร, 2023)
Coating tomato seeds with plant nutrients can stimulate seed germination and seedling growth. However, there are few reports on shelf life after seeds are coated with plant nutrients. The good condition of seed storage is useful through increasing longevity and providing high seed quality. Therefore, this research aimed to study 6-month seed longevity after tomato seeds were coated in different ways. Tomato seeds were coated with different plant nutrient formulations (PNF) containing N, P, K, Ca, Mg, Fe, B, Mn, Cu and Zn. The five seed treatments were as follows: (1) uncoated seeds as a control (C), (2) Only polymer coated the seeds (PF0), seeds coated with a polymer mixture with a plant nutrition formulation (PNF) including (3) 1-fold PNF(PF1), (4) 4-fold PNF(PF4) and (5) 16-fold PNF(PF16). The coating polymer was 3% PVP-K90 and 1% PEG 6000 and it was used at the rate of 200 ml per kg in each treatment. All treatments were stored in a controlled chamber at 15oC with 50% RH and ambient conditions at room temperature and relative humidity for 6 months. Every 3 months all treatments were tested for percentage of seed germination, speed of seedling emergence, seedling length and seedling dry weight tested in laboratory and greenhouse. The results showed that in both storage methods, the percentage of seed germination of PF4 and PF16 tested in the laboratory were higher than control. The root length of PF16 seedlings was affected by high acidity in both conditions, but it stimulated shoot length resulting in the highest in total seedling length tested in the laboratory. Both of all storage methods and test conditions seedling dry weight were increased with increased PNF concentrations. All treatments stored in a controlled chamber for 6 months exhibited higher seed quality than ambient conditions,